The Use of Interjections and Emotional Expressions in the Novel Me Before You - Parasian, Nehemia Anugrah (Journal of Language, Literature and Teaching, 2025)
Interjection is one of the language elements that represent spontaneous and direct expression of emotion. This research aims to describe the form, meaning, and function of interjections in the novel Me Before You by Jojo Moyes, and relate them to the category of emotional expression. The research method used is descriptive qualitative with semantic approach. The research data are sentences and dialogs containing interjections in the novel. The data collection technique is done by reading the text thoroughly, recording the interjections that appear, and classifying them into interjection categories based on Wierzbicka's theory. Data analysis includes identifying interjection forms, explaining literal and contextual meanings, determining the function of interjections in the storyline, and mapping emotion categories based on Jovanovic’s framework. The results show that emotive interjections in the novel mostly represent the emotions of surprise, anger, fear, contempt, and pity; volitive interjections express impatience, enthusiasm, irritation, and sympathy; while cognitive interjections signify triumph, wonder, approval, confusion, and surprise. Interjections not only function as expressions of emotion, but also support character development, create story atmosphere, and move the plot. This research is expected to enrich the semantic study of interjections in literary texts, as well as to serve as a reference.